Kebijakan Peningkatan Kualitas Perencanaan Anggaran Kementerian Agama - Roihan, Rijal (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper describes that Work Plan and Budget (RKA) is one of the instruments in the implementation of the State Budget (APBN) to support national development. Each Ministry/Institution (K/L) prepares the RKA as a reference in budget implementation based on their respective needs to achieve the goals and targets that have been set. However, in its implementation, sometimes there is a gap between the RKA and budget implementation, which can hinder the achievement of goals. This paper aims to identify and analyze the causes of this gap. The methodology used is a qualitative descriptive approach, which includes literature studies, interviews, and participatory observations in budget preparation. The discussion of the paper shows that several factors contribute to the mismatch between planning documents and budget realization. The quality of planning documents often does not reflect real needs and policy priorities. In addition, the lack of accurate and up-to-date data is a challenge in preparing a quality RKA. The use of information systems that are not optimal is also a problem because many processes still rely on manual methods that are prone to errors. This paper provides suggestions in the form of developing an integrated information system that can improve accuracy, transparency, and efficiency in the budget planning and implementation process.